A Neonatal Resuscitation Curriculum in Malawi, Africa: Did It Change In-Hospital Mortality?. (20th November 2011) - Hole, Michael K.; Olmsted, Keely; Kiromera, Athanase; Chamberlain, Lisa
Abstract : Objective . The WHO estimates that 99% of the 3.8 million neonatal deaths occur in developing countries. Neonatal resuscitation training was implemented in Namitete, Malawi. The study's objective was to evaluate the training's impact on hospital staff and neonatal mortality rates. Study Design . Pre-/postcurricular surveys of trainee attitude, knowledge, and skills were analyzed. An observational, longitudinal study of secondary data assessed neonatal mortality. Result . All trainees' (n = 18 ) outcomes improved, (P = 0.02 ). Neonatal mortality did not change. There were 3449 births preintervention, 3515 postintervention. Neonatal mortality was 20.9 deaths per 1000 live births preintervention and 21.9/1000 postintervention, (P = 0.86 ). Conclusion . Short-term pre-/postintervention evaluations frequently reveal positive results, as ours did. Short-term pre- and postintervention evaluations should be interpreted cautiously. Whenever possible, clinical outcomes such as in-hospital mortality should be additionally assessed. More rigorous evaluation strategies should be applied to training programs requiring longitudinal relationships with international community partners.